Nilai Kultural dan Pendidikan dalam Tradisi Jawa Bubakan - Munifah, Siti (Jurnal Bahasa dan Sastra, 2021)
This study aims to describe cultural and educational values in the bubakan tradition. The bubakan tradition is a Javanese traditional ceremony that is carried out when parents have to marry their first child or the eldest child. This research is a field research (field research) that focuses on exploring the cultural meaning and educational value in symbols used in the ritual of bubakan. Data were collected through observation and document study. The data were then analyzed descriptively according to Miles and Hubberman’s interactive model of data analysis. Based on the results of the study, it was found that the cultural meaning of bubakan is as follows: (1) a sign of gratitude because parents can carry out their obligations, (2) a prayer asking for safety, health, and abundant sustenance, (3) psychologically to get peace, tranquility, and (4) remove all obstacles in his life. While the educational values found by the researchers were as follows: (1) spiritual education values, (2) socio-cultural education values, and (3) character education values. Bubakan educates Javanese people on the importance of getting closer to God Almighty, having social awareness through charity, and having a better personality or character such as always respecting and honoring parents, being a useful person, having a strong will, and never giving up.